Методика комплексної оцінки кадрового потенціалу вищого навчального закладу - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д.; Воронюк, О. І. (Ways to Improve Construction Efficiency, 2014)
A methodological approach to the evaluation of personnel, potential-the potential of higher education institutions (HEIs), which allows to evaluate personal qualities and specific features of the teaching staff at the university development strategy.